Methodology to quantify apparent losses versus real losses in narrow tabular precious metal ore flows - Mhlongo, Adolph (My University, 2021)
This research examined the methodology to quantify apparent losses versus real losses in narrow tabular precious metal ore flows, and to investigate the uncertainty in the estimations used to determine the monthly and annual MCF. The apparent losses are caused by incorrect sampling, incorrect survey measurements, geological modeling, incorrect relative density applied, and incorrect assaying. Real losses are a result of fines trapped in the stopes footwall cracks, sweepings not continuously done with blasting, spillages, gold theft, and spillage during tramming. Due to the measurement uncertainties used to determine the metal called for in the MCF calculation, these uncertainties could then be used in a Monte Carlo simulation to estimate the range of the MCF and thus estimate the real and apparent loss split. Both apparent grade and real grade loss occurred in the period under review for Sibanye-Stillwater gold operations. Sibanye-Stillwater gold mines operations, grade loss amounts to 21%, while the tonnage gain amounts to 6.3%, with the survey shortfall of +5.6% ,and the MCF of 84% for 2017. It is both apparent and real gain for the tonnages and apparent and real loss on the grade which affects the MCF, which ultimately affects the revenue, which equates to R4,18bn for the year under review. It has been shown that there are losses, and are between 10 and 14% on the Sibanye-Stillwater gold mines. This range includes the uncertainties in estimations. Monte Carlo simulation is been used to determine the range of the MCF due to estimation uncertainties. It can be concluded that the real losses are at least 10%
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2021